Hypothalamic Hamartoma Associated with a Craniopharyngeal Canal - Kizilkilic, Osman; Yalcin, Ozlem; Yildirim, Tulin; Sener, Levent; Parmaksiz, Gonul; Erdogan, Bulent (American Journal of Neuroradiology, 2005)
Summary: Hypothalamic hamartoma is a rare congenital lesion. We present the case of a 7-year-old girl who suffered from precocious puberty, the cause of which was diagnosed by using MR imaging and CT as pedunculated hypothalamic hamartoma associated with a large craniopharyngeal canal and sellar spine mimicking pituitary duplication.